2018
DOI: 10.1177/1354816618812565
|View full text |Cite
|
Sign up to set email alerts
|

Tourism–growth nexus and spatial spillovers: Evidence from Greece

Abstract: In this research note, we reconsider the tourism–growth nexus by accounting for spillover effects between regional tourism development and regional economic growth. For this purpose, we utilize spatial panel econometric techniques to measure the above effects in 49 Greek prefectures during the period 2010–2014. Our findings indicate strong short-run and long-run spillover effects, suggesting that policymakers should consider regional tourism development as a key factor for boosting national economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…In addition, whether domestic tourism or inbound tourism and direct effects or spillover effects, this study found that the direction of the long-term effects is consistent with that of the short-term effects, but the strength of the long-term effects is significantly greater than that of the short-term effects, which is consistent with the previous studies (Eleftheriou and Sambracos, 2018;Zhao and Quan, 2011). This is because in the long-term, a multiplier chain effect formed by tourism consumption gradually appears, which promotes an increase in the direct and indirect income of tourism, thereby significantly stimulating economic growth (Zhao and Quan, 2011).…”
Section: Effects Of Tourism Development On Economic Growthsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, whether domestic tourism or inbound tourism and direct effects or spillover effects, this study found that the direction of the long-term effects is consistent with that of the short-term effects, but the strength of the long-term effects is significantly greater than that of the short-term effects, which is consistent with the previous studies (Eleftheriou and Sambracos, 2018;Zhao and Quan, 2011). This is because in the long-term, a multiplier chain effect formed by tourism consumption gradually appears, which promotes an increase in the direct and indirect income of tourism, thereby significantly stimulating economic growth (Zhao and Quan, 2011).…”
Section: Effects Of Tourism Development On Economic Growthsupporting
confidence: 91%
“…We further graphed the histogram and the quantile-quantile plot of lnTI (Online Appendix 1), which showed that this variable approximately obeys a normal distribution. Therefore, as in previous studies (Eleftheriou and Sambracos, 2018;Ma et al, 2015;Yang and Filk, 2014), although the standard deviation is greater than the mean, the data still meet the conditions of model parameter estimation, and the results are reliable.…”
Section: Data Collection and Summary Statisticssupporting
confidence: 79%
See 2 more Smart Citations
“…The results show that city satisfaction exerts a significantly positive, spatial spillover effect on GDP growth in adjacent cities. Eleftheriou and Sambracos (2019) analyzed the tourism–growth nexus by accounting for the spillover effects and verified the existence of spillover effects. Chen et al (2020) investigated the spatial effect of tourism on the regional ecological efficiency and discovered that tourism development exerted different spatial spillover effects across different periods.…”
Section: Literature Reviewmentioning
confidence: 99%